Reflujo vesicoureteral. Estudio de 122 pacientes. - Rodríguez Fernández, Olga; Ores Viego, José A.; Ramos Padrón, Lourdes; Martínez Palma, Miguel (Revista Cubana de Pediatría, 2024)
Analizar la situación con reflujo vesicouretetal primario.